2019
DOI: 10.1111/luts.12262
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of refractory overactive bladder

Abstract: Overactive bladder (OAB) is a common condition. The International Continence Society defines OAB as a symptom complex characterized by urgency with or without urge incontinence, usually with frequency and nocturia. The first‐line treatment for OAB includes behavioral therapy, such as caffeine reduction, fluid intake modification, weight reduction, bladder training, and pelvic floor muscle training, as well as treatment with antimuscarinic or β3‐adrenoceptor agonist medications. However, less than half of all c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 68 publications
0
33
0
4
Order By: Relevance
“…The prevalence of refractory OAB is unknown. Patients with refractory OAB may have underlying pathophysiologies not resolved after the initial therapy, including occult neurogenic bladder, undetected BOO, urethral‐related OAB, aging process and urothelial dysfunction, chronic bladder ischemia, chronic bladder inflammation, central sensitization, and autonomic dysfunction …”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of refractory OAB is unknown. Patients with refractory OAB may have underlying pathophysiologies not resolved after the initial therapy, including occult neurogenic bladder, undetected BOO, urethral‐related OAB, aging process and urothelial dysfunction, chronic bladder ischemia, chronic bladder inflammation, central sensitization, and autonomic dysfunction …”
Section: Introductionmentioning
confidence: 99%
“…Occult neurogenic bladder, undetected BOO, provoked DO due to urethral incompetence, aging or diseases, chronic bladder ischemia, chronic bladder inflammation, central nervous system (CNS) sensitization, and autonomic dysfunction are possible etiologies of refractory OAB. [1] The bladder urothelium and afferent nerves express transient receptor potential vanilloid receptor 1 (TRPV1), the purinergic receptor P2X3, the sensory neuropeptides substance P, and calcitonin gene-related peptide (CGRP). [13][14][15] These receptors are believed to be involved in the afferent pathways that control bladder sensation and urinary volume reflexes [16].…”
Section: Pathophysiology Of Bladder Oversensitivitymentioning
confidence: 99%
“…Currently, there is no definite definition nor specific medication targeting bladder oversensitivity. Bladder oversensitivity is usually existent with other lower urinary tract disorders (LUTD) such as bacterial cystitis, ketamine cystitis, interstitial cystitis (IC), bladder outlet obstruction (BOO), overactive bladder syndrome (OAB), idiopathic detrusor overactivity (DO), neurogenic DO (NDO); or systemic diseases such as diabetes mellitus, end-stage renal disease, or congestive heart failure [1]. Antimuscarinics or beta-3 adrenoceptor agonists have therapeutic effects on OAB and DO and also have some effect on reducing bladder oversensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Lower urinary tract symptoms including overactive bladder (OAB) are common urologic disorders in the elderly [10][11][12][13][14][15][16][17][18][19][20] and several studies have suggested an association of falls with OAB. 21 The OAB symptoms are the leading causes of sleep disturbance 13,22,23 and are associated with frailty. 12 Furthermore, poor sleep quality and frailty are associated with an increased risk of falls.…”
Section: Introductionmentioning
confidence: 99%